Ідеографічна класифікація галузевої лексики в укладанні електронного словника (на прикладі гідротурбінної термінології) - Купріянов, Євген Валерійович (Харкiвський нацiональний унiверситет iм. В. Н. Каразiна, 2010)
Thesaurus as a way of compiling special-purpose electronic dictionary (on the example ofhydraulic turbine terminology). The present article is devoted to ideographic classification as a way of representing special-purpose terminology in multilingual electronic dictionary on hydraulic turbines, particular examples of performing this classification are proposed, the topicality of ideographic classification is justified in pragmatic aspect, namely in overcoming the difficulties connected with the complicated structure of hydraulic turbine term system
Keywords: терміносистема; співвіднесеність термінів; базисні терміни; лексичні одиниці; тезаурус; вузькоспеціалізована лексика